Budapest az európai nagyvárosi rendszerben - Enyedi, György (Tér és Társadalom, 1992)
During the last decades an integrated, transnational metropolitan system has developed in Europe. The bakcbone of this system has been formed by West-European areas. At present, Mediterranean metropolises – as Madrid, Barcelona and Lisboa – are joining the urban core of Europe. In Central Europe, this urban core has already an outer ring: Munich, Zurich, Milan and Vienna. This paper analyzes the possibilities of the Hungarian capital to join the European metropolitan system. It focuses on three aspects: Traditions of Budapest in macro-regional functions; How can the city's infrastructure fulfill intemational functions; Is the urban society ready to function similarly to the European metropolitan societies? In the long history of the Hungarian capital, there were only two periods when the city had significant role in Europe. The first was in the late Middle Ages (14th and 15th centuries), the second at the turn of the 20th century (between 1870 and 1914). In this latter period, Budapest was tumed into a modern metropolis. Between 1870 and 1914, Budapest was the second fastest-growing city of Europe (after Berlin). Its population tripled ín four decades and incrased to 1 million by 1910. In 1870, the Hungarian capital was a mediumsize city, the 17th largest in Europe. In 1910, the city ranked 8th in Europe, it was larger than Rome, Madrid and Milan. This growth was carefully planned and matched by infrastructural development. The city developed a large set of international relations in the early 20th century. Budapest controlled the Carpathian Basin and had close economic relations with the Balkans. World War I ended with the Paris Peace Treaty, which dismembered Austria-Hungary. Budapest became the capital city of a small country, whose economy had stagnated for decades. The same remained true during the socialist period. Budapest had no international influence. At the same time, the size and the national importance of the city strengthened. The concentration of high-level functions and richess into Budapest was unhealthy from the point of view of the country's regional structure – but it prepared the city for taking back some of its earlier international functions. Budapest owns the preconditions for the transition into a European metropolis. The city has 2 million inhabitants, she has a colourful cultural life, and the infrastructure for tourism. The means for receiving foreign business headquarters are available, although their standard is not high enough. Also, the city's population is well-trained: Budapest concentrates 70 % of the R+D employees, 50% of the teaching staff of higher education, and 79 % of leading business managers of the country. Budapest has been appreciated by foreign investors since 1989: 30 % of the total sum invested by Western capitalists in the European post-socialist countries was concentrated in this single city. Society of Budapest is ready to join the European metropolises. Its structure – with the large second economy, a sizeable elite, but a relatively weak middle class – is more similar to the socialist system, often against the official urban policy, using informal methods and mechanisms. For instance, the social prestige of the place of residence has remained important, hence segregation is strong. The „homogenous socialist society" was short-lived in Budapest. After the 1956 Revolution, the communist regime offered some – limited – possibilities for embourgeoisement and for individual initiatives – for the sake of social peace. The socialist system did not destroy entirely the capitalist urban society, rather hibernated it. It was partly kept alive half-legally, in the "parallel" or "shade" society. These are all advantages for Budapest now: market economy, and new institutions are integrated without major shocks. The continuity also means the preservation of some anachronistic elements (e.g. weak middle class, strong personal interdependence of the political, cultural and economic elites).